2019
DOI: 10.1016/j.scitotenv.2018.08.346
|View full text |Cite
|
Sign up to set email alerts
|

Acetaminophen detoxification in cucumber plants via induction of glutathione S-transferases

Abstract: Many pharmaceutical and personal care products (PPCPs) enter agroecosystems during reuse of treated wastewater and biosolids, presenting potential impacts on plant development. Here, acetaminophen, one of the most-used pharmaceuticals, was used to explore roles of glutathione (GSH) conjugation in its biotransformation in crop plants. Acetaminophen was taken up by plants, and conjugated quickly with GSH. After exposure to 5 mg L acetaminophen for 144 h, GSH-acetaminophen conjugates were 15.2 ± 1.3 nmol g and 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 54 publications
0
38
0
Order By: Relevance
“…Effective and reliable detection of pharmaceutical drugs is a remaining goal in Analytical Chemistry because of their potential environmental impact. Acetaminophen is an extensively used pharmaceutical, which cannot be efficiently removed from treated waste water and, therefore, tends to reach agricultural activity even at the ppm level [69]. Acetaminophen detection has been carried out using several different techniques, including electrochemical methods, infrared spectroscopy, chromatography and electrophoresis, among many others [70][71][72][73][74], which are certainly complex and highly-time consuming.…”
Section: (D) Acetaminophen (Amp)mentioning
confidence: 99%
“…Effective and reliable detection of pharmaceutical drugs is a remaining goal in Analytical Chemistry because of their potential environmental impact. Acetaminophen is an extensively used pharmaceutical, which cannot be efficiently removed from treated waste water and, therefore, tends to reach agricultural activity even at the ppm level [69]. Acetaminophen detection has been carried out using several different techniques, including electrochemical methods, infrared spectroscopy, chromatography and electrophoresis, among many others [70][71][72][73][74], which are certainly complex and highly-time consuming.…”
Section: (D) Acetaminophen (Amp)mentioning
confidence: 99%
“…Using wastewater may affect human health as well as the environment because of its content of salts, heavy metals, bacteria and viruses, and contaminants of emerging concern (CECs), depending on the source of wastewater, its composition, and treatment technique [6]. Therefore, many laboratory studies investigated the potential uptake, translocation and accumulation of CECs in plants even at high concentrations that do not exist actually in nature [4,[22][23][24][25][26][27][28][29]. Similarly, Naser et al [30] also reported an accumulation of some heavy metals in leafy vegetables irrigated by municipal and industrial untreated wastewater.…”
Section: Introductionmentioning
confidence: 99%
“…Based on animal detoxification mechanisms of organic xenobiotics, related metabolic pathways were explored in plants, and similar responses were described (including antioxidant responses to cope with oxidative stress). Although organic xenobiotic metabolization and transformation by plants remain incompletely characterized, a model has been proposed (Edwards et al, 2005;Edwards et al, 2011;El Amrani et al, 2015;Sun et al, 2019) with three major steps: (1) signaling, (2) transport and transformation, and (3) compartmentalization. This model involves a myriad of enzymes from the xenome, among alpha-beta hydrolases (e.g.…”
Section: Introductionmentioning
confidence: 99%